Konsep Diri dan Tingkat Burnout pada Karyawan yang Bekerja di Instansi Pelayanan Masyarakat - Rina Amelia; Zulkarnain Zulkarnain (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2005)
The aim of this study is to investigate the relationship between Self concept and Burnout. The study was a field research which data collected through Scale of Self Concept and Scale of Burnout. The subject were employees of Dinas Pencegah dan Pemadam Kebakaran (DP2K), ones of Public service in Medan. The number of subject was 85. The result show that was a negative correlation between self concept and burnout (rxy = -0.583, p < 0.01). Self Concept contributes  34% to Burnout. It means that, the positive of self concept, the lower of burnout. In addition, the finding also shows there was a significant difference in burnout based on worked period (F = 3.431, p < 0.05). Employees who have worked period 11-20 years, significantly tendency to burnout than employees who have worked period 2-10 years and 21-28 years.Keywords : Self Concept, Burnout.